Implementation of basic life support outside the hospital through video training - Insana Maria; Annalia Wardhani (University of Merdeka Malang, 2023)
Emergency actions are not only carried out by medical teams but can also be performed by the general public, especially in life-saving actions such as basic life support. Emergency situations can occur anywhere and at any time, with 85% of emergency incidents known to occur outside of hospitals. With this understanding, efforts are needed to improve public knowledge about the implementation of basic life support in order to facilitate activities using video training for basic life support. The goal of this community service activity is to improve the community's ability to implement basic life support in emergency cases at home. The activity was carried out in Sungai Alat village, Astambul sub-district, with 60 participants facilitated by two speakers and five students. The stages of the activity included observation, coordination, video training creation, implementation, and evaluation. As a result of the activity, the majority of the participants had good knowledge of implementing basic life support and were satisfied with the implementation of the activity. Community service through video training provided ease in implementing basic life support actions.